2008
DOI: 10.1159/000151507
|View full text |Cite
|
Sign up to set email alerts
|

Allergic Sensitization to Bovine β-Lactoglobulin: Comparison between Germ-Free and Conventional BALB/c Mice

Abstract: Background: The ‘hygiene hypothesis’ suggests that high hygienic standards met in western countries lead to a lack of microbial exposure, thus promoting the development of atopy by preventing the proper maturation of the immune system. Germ-free animals are deprived of the immune stimulation that occurs during postnatal gut colonization by commensal bacteria. Germ-free mice could thereby provide an attractive model for studying the impact of gut microbiota on the development of Th2-mediated disorders such as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 64 publications
2
30
1
Order By: Relevance
“…Previous studies have also suggested that GF mice are more susceptible to allergic sensitization than CV mice [9,10]. Our present study, using a model in which the antigen was exclusively fed, without any systemic sensitization by intraperitoneal or intraveneous administration, has revealed that higher serum antibody responses (OVA-specific IgE, IgG1 and IgG2a) are induced in GF mice than in CV animals (Fig.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Previous studies have also suggested that GF mice are more susceptible to allergic sensitization than CV mice [9,10]. Our present study, using a model in which the antigen was exclusively fed, without any systemic sensitization by intraperitoneal or intraveneous administration, has revealed that higher serum antibody responses (OVA-specific IgE, IgG1 and IgG2a) are induced in GF mice than in CV animals (Fig.…”
Section: Discussionsupporting
confidence: 63%
“…As a consequence, germ-free (GF) animals, which lack indigenous bacteria in their gastrointestinal tract, provide valuable tools for analyzing the direct modulation of the immune system by such bacteria. Indeed, when such mice are intraperitoneally immunized with an antigen plus adjuvant, more antigen-specific antibodies are produced in the serum of GF mice than in that of specific-pathogen free (SPF) animals [9,10]. In addition, it has been reported that oral administration of various antigens prior to immunization with those same antigens induces oral tolerance in conventional (CV) mice but not in GF mice [1,9,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In mice, experiments using germ-free or antibiotic-treated mice have demonstrated an increased food-allergen sensitivity, elevated serum-specific IgE, and increased levels of circulating basophils. 54,55 In humans, differences in the intestinal flora of allergic versus nonallergic children have been noted. 56 Investigators have identified certain microbes that promote the development of Tregs and certain microbes that promote the skewing toward allergic sensitization.…”
Section: Pathophysiology Of Food Allergymentioning
confidence: 99%
“…41 Many recent studies have suggested that the microbiota may be a disease promoting factor in food intolerances or sensitivities. Evidence from animal models show that germ-free mice are more susceptible to oral sensitization to cow's milk protein, 42,43 and OVA-induced allergy. 44 Oral sensitization to OVA led to altered intestinal microbial composition in genetically susceptible mice, which was not evident in wild-type (WT) mice.…”
Section: Role Of the Microbiota On Immune Development And Homeostasismentioning
confidence: 99%